Guidelines for Conserving Kolae Boat Wisdom in the Southern Border Provinces - Tongsri, Prachuab; Nongrat, Sanchai (Journal of Social Sciences and Humanities Research in Asia, 2022)
The objective of this research is to create a guideline of Kolae boat’s folk wisdom conservation in the southern border provinces, and it used the qualitative research methodology with research areas of Paseyawo Community, Pattani Province, Ban Thon Community and Sala Mai Community, Narathiwat Province. There were 24 informants divided into 6 groups: folk instructors who passed on the boat’s wisdom, recipients of the boat’s wisdom, Kolae boat’s owners, community leaders, academics, and government officials. In-depth interview and focus group discussion were used for content analysis. The research found that the Kolae boat has been a unique identity of fishermen in the lower southern provinces from the past to the present. The decorations and paintings on the boat are priceless works of art because its uniqueness is obvious and valuable, demonstrating the fine folk wisdom of the southern border provinces. Currently, the uses of the boat are both for fishing and tourism. In conclusion, the guidelines of Kolae boat’s folk wisdom conservation in the southern border provinces consist of 1) passing on the boat’s wisdom to own children and young, new generation 2) promoting collaborative activities to conserve the boat’s wisdom 3) promoting and supporting of the boat’s wisdom from communities and government organizations, and 4) gathering knowledge about the boat’s wisdom to be a source of Kolae boat’s learning and information collecting.